2004
DOI: 10.1007/s00414-004-0488-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of three Amerindian populations from Hidalgo State (Mexico) by 15 STR-PCR polymorphisms

Abstract: The purpose of this study is to report allele frequency data of three ethnic Amerindian population samples: the Otomi (Hna-hnu) from eastern Sierra Madre and Ixmiquilpan valley and the Huasteco from La Huasteca. These groups were characterised by 15 STR-PCR polymorphisms (HumTH01, HumvWA, D18S51, HumTPOX, D19S433, D16S539, D13S317, D8S1179, D7S820, D5S818, HumFGA, CSF1PO, D2S1338, D3S1358 and D21S11). No significant deviations in observed allelic frequencies from Hardy-Weinberg equilibrium were found for all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
22
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 8 publications
6
22
1
Order By: Relevance
“…The alleles most frequent in our three Mexican groups also are typical Amerindian populations (Table 3). The frequencies of the STR alleles found in this study are in agreement with previous studies in Mexican Native communities [17], [18], this is further detailed in Table S1. Of special interest to us were STR markers of persons colonized with Asian-related H. pylori strains marked in grey in Table 3, one Huichol (368H), one Otomi (23O) and one Tarahumara (590T).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The alleles most frequent in our three Mexican groups also are typical Amerindian populations (Table 3). The frequencies of the STR alleles found in this study are in agreement with previous studies in Mexican Native communities [17], [18], this is further detailed in Table S1. Of special interest to us were STR markers of persons colonized with Asian-related H. pylori strains marked in grey in Table 3, one Huichol (368H), one Otomi (23O) and one Tarahumara (590T).…”
Section: Resultssupporting
confidence: 92%
“…These frequencies are similar to previous studies in Mexican native and mestizo groups, and confirm the admixture of pre-Spaniard native Mexican communities with European population, and to a much lesser extent with African markers [26]. The frequency of STRs alleles in the populations studied also demonstrated similarities with previous studies in Mexican Natives [18], [19]. Thus, genotyping of individuals from the three Mexican native groups studied document that although all have Amerindian markers, each population is different based on the frequency of mtDNA, Y-chromosome and STRs markers.…”
Section: Discussionsupporting
confidence: 90%
“…The correct interpretation of CODIS-STR-generated DNA profiles in forensic casework requires knowledge of the allele distribution and some statistical parameters in the population in which the system will be applied; thus, worldwide-population STR datasets have been generated for this purpose. In Mexico, despite the large number of Native groups, only a few molecular studies have been conducted with autosomal STR loci in these populations (Rangel-Villalobos et al 2000;Sánchez et al 2005;Barrot et al 2005;Ibarra-Rivera et al 2008;González-Martín et al 2008).…”
Section: Introductionmentioning
confidence: 98%
“…These studies have shown a substantial contribution of Native American ancestry to extant Mexican Mestizo populations, supported by additional studies based on mtDNA sequences (González-Oliver et al 2001;Green et al 2000;Kemp et al 2010;Peñaloza-Espinosa et al 2007;Sandoval et al 2009;Torroni et al 1994). Other studies have also described the paternal genetic diversity in Mexican 4 indigenous groups (Barrot et al 2005;Felix-Lopez et al 2006;Kemp et al 2010;PaezRiberos et al 2006;Rangel-Villalobos et al 2000); however, a better understanding could be gained by putting this characterization into context with the continental landscape. Previous studies on continental genetic structure identified by autosomal markers (Wang et al 2007;Yang et al 2010), have reported a North-to-South reduction of diversity in the Americas, consistent with early studies based on Y-chromosome diversity showing patterns of low haplotypic diversity in Native American populations (Ruiz-Linares et al 1999;Salzano 2002;Underhill et al 2001).…”
Section: Introductionmentioning
confidence: 99%